Mind the cell: Seasonal variation in telomere length mirrors changes in leucocyte profile. Issue 20 (8th September 2017) - Beaulieu, Michaël; Benoit, Laure; Abaga, Steven; Kappeler, Peter M.; Charpentier, Marie J. E.
Abstract: Leucocytes are typically considered as a whole in studies examining telomere dynamics in mammals. Such an approach may be precarious, as leucocytes represent the only nucleated blood cells in mammals, their composition varies temporally, and telomere length differs between leucocyte types. To highlight this limitation, we examined here whether seasonal variation in leucocyte composition was related to variation in telomere length in free‐ranging mandrills ( Mandrilllus sphinx ). We found that the leucocyte profile of mandrills varied seasonally, with lower lymphocyte proportion being observed during the long dry season presumably because of the combined effects of high nematode infection and stress at that time of the year. Interestingly, this low lymphocyte proportion during the long dry season was associated with shorter telomeres. Accordingly, based on longitudinal data, we found that seasonal changes in lymphocyte proportion were reflected by corresponding seasonal variation in telomere length. Overall, these results suggest that variation in lymphocyte proportion in blood can significantly affect telomere measurements in mammals. However, lymphocyte proportion did not entirely explain variation in telomere length. For instance, a lower lymphocyte proportion with age could not fully explain shorter telomeres in older individuals. Overall, our results show that telomere length and leucocyte profile are strongly although imperfectly intertwined, which may obscure the relationship between telomere dynamics and ageing processes in mammals.